Chemical, mechanical and biological properties of contemporary composite surface sealers. Issue 12 (December 2015) - Anagnostou, Maria; Mountouris, George; Silikas, Nick; Kletsas, Dimitris; Eliades, George
Abstract: Objectives: To evaluate the chemical, mechanical, and biological properties of modern composite surface sealers (CSS) having different compositions. Methods: The CSS products tested were Biscover LV (BC), Durafinish (DF), G-Coat Plus (GC), and Permaseal (PS). The tests performed were: (A): degree of conversion (DC%) by ATR-FTIR spectroscopy; (B): thickness of O2 -inhibition layer by transmission optical microscopy; (C): surface hardness, 10 min after irradiation and following 1 week water storage, employing a Vickers indenter (VHN); (D): color (Δ E *) and gloss changes (ΔGU) after toothbrush abrasion, using L * a * b * colorimetry and glossimetry; (E): accelerated wear (GC, PS only) by an OHSU wear simulator plus 3D profilometric analysis, and (F): cytotoxicity testing of aqueous CSS eluents on human gingival fibroblast cultures employing the methyl- 3 H thymidine DNA labeling method. Statistical analyses included 1-way (A, B, Δ E *, ΔGU) and 2-way (C, F) ANOVAs, plus Tukey post hoc tests. Student's t -test was used to evaluate the results of the accelerated wear test ( α  = 0.05 for all). Results: The rankings of the statistical significant differences were: (A) PS (64.9) > DF, BC, GC (56.1–53.9) DC%; (B) DF, PS (12.3, 9.8) > GC, BC (5.2, 4.8) μm; (C): GC (37.6) > BC, DF (32.6, 31.1) > PS (26.6) VHN (10 min/dry) and BC, DF (29.3, 28.7) > GC(26.5) > PS(21.6) VHN (1w/water), with no significant material/storage condition interaction; (D): no differences were found among GC, DF, BC, PS (0.67–1.11) Δ E *, with all values within the visually acceptable range and PS, BC (32.8, 29.4) > GC, DF (19.4, 12.9) ΔGU; (E): no differences were found between GC and PS in volume loss (0.10, 0.11 mm 3 ), maximum (113.9, 130.5 μm) and mean wear depths (30.3, 27.5 μm); (F): at 1% v/v concentration, DF showed toxicity (23% vital cells vs 95–102% for others). However, at 5% v/v concentration DF (0%) and BC (9%) were the most toxic, whereas GC (58%) and PS (56%) showed moderate toxicity. Significance: Important chemical, mechanical, and biological properties exist among the CSS tested, which may affect their clinical performance.